Factors contributing to sleep disturbances and excessive daytime sleepiness in patients with Parkinson's disease - Ogaki, Keitaro; Fujita, Hiroaki; Nozawa, Narihiro; Shiina, Tomohiko; Sakuramoto, Hirotaka; Suzuki, Keisuke (Frontiers in Neurology, 2023)
Background Sleep disturbances and excessive daytime sleepiness (EDS) are common non-motor symptoms in patients with Parkinson's disease (PD). The purpose of this study was to identify the contributors to sleep disturbances, including insomnia, restless legs syndrome, rapid eye movement sleep behavior disorder (RBD), sleep-disordered breathing, nocturnal akinesia and EDS, in patients with PD. Methods We conducted a cross-sectional study including 128 consecutive Japanese patients with PD. Sleep disturbances and EDS were defined as a PD Sleep Scale-2 (PDSS-2) total score ≥15 and an Epworth Sleepiness Scale (ESS) score >10, respectively. The patients were divided into four groups according to the presence or absence of sleep disturbances and EDS. We evaluated the disease severity, motor symptoms, cognition, olfactory test, the Scales for Outcomes in PD-Autonomic dysfunction (SCOPA-AUT), the Beck Depression Inventory-II (BDI-II), and the RBD Screening Questionnaire Japanese version (RBDSQ-J). Results Of 128 patients, 64 had neither EDS nor sleep disturbances, 29 had sleep disturbances without EDS, 14 had EDS without sleep disturbances, and 21 had both EDS and sleep disturbances. Patients with sleep disturbances had higher BDI-II scores than those without sleep disturbances. Probable RBD was more frequent in patients with both sleep disturbances and EDS than in those with neither EDS nor sleep disturbances. The SCOPA-AUT score was lower in patients with neither EDS nor sleep disturbances than in patients in the other three groups. Using multivariable logistic regression analysis with neither sleep disturbances nor EDS as a reference group, that the SCOPA-AUT score was an independent contributor to sleep disturbances (adjusted OR, 1.192; 95% CI, 1.065–1.333; P = 0.002) or EDS (OR, 1.245; 95% CI, 1.087–1.424; P = 0.001) and that the BDI-II (OR, 1.121; 95% CI, 1.021–1.230; P = 0.016) and RBDSQ-J scores (OR, 1.235; 95% CI, 1.007–1.516; P = 0.043) as well as the SCOPA-AUT score (OR, 1.137; 95% CI, 1.006–1.285; P = 0.040) were independent contributors to both sleep disturbances and EDS. Conclusions Autonomic symptoms were associated with patients with sleep disturbances or EDS, and depressive and RBD symptoms in addition to autonomic symptoms were associated with patients with both sleep disturbances and EDS.